Good corporate governance and firm value: the mediating role of internet financial reporting / Indri Kartika ... [et al.] - -, Indri Kartika; Sulistyo, Heru; Indriastuti, Maya; -, Mutamimah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study enriches the corporate governance and firm value literature by testing internet financial reporting as a mediating variable. This study used 353 service companies listed on the Indonesian Stock Exchange in 2020 and analyzed it by using the SmartPLS. Corporate governance used the variables of the board of commissioners and audit committee as measured by the number of meetings. Internet financial reporting was measured by four components (namely content, timeliness, technology use, and user support). Firm value was measured by Tobin's Q. The results of this study revealed that the activities of the board of commissioners, the activities of the audit committee, and Internet financial reporting can increase investor confidence and firm value in service companies in Indonesia. This research contributes to the literature on corporate governance, internet financial reporting, and firm value. Corporate governance mechanisms can encourage the application of Internet financial reporting (accurate, timely, and attractive manner) and increase corporate value. Thus, service companies should always be committed to corporate governance mechanisms and Internet financial reporting to gain public trust. The government needs to encourage the implementation of good corporate governance through the activities of commissioners and audit committees and also improve financial reporting regulations through Internet financial reporting to facilitate investors to obtain accurate and timely information.